All-silicon polarized light source based on electrically excited whispering gallery modes in inversely tapered photonic resonators - Schmitt, Sebastian W.; Schwarzburg, Klaus; Sarau, George; Christiansen, Silke H.; Wiesner, Sven; Dubourdieu, Catherine (APL Materials, 2020)
As a result of its indirect bandgap, emitting photons from silicon in an efficient way remains challenging. Silicon light emitters that can be integrated seamlessly on a CMOS platform have been demonstrated; however, none satisfies an ensemble of key requirements such as a small footprint, room-temperature operation at low voltages, and emission of narrow and polarized lines with a high spectral power density in the near-infrared range. Here, we present an all-silicon electrically driven light emitting diode that consists of an inversely tapered half-ellipsoidal silicon photonic resonator containing a p-n junction used to excite whispering gallery modes (WGMs) inside the resonator. Under low voltage operation at room temperature, such a photonic silicon light-emitting diode exhibits a band-edge emission (900-1300 nm) with a wall-plug efficiency of 10-4. The emitted spectrum is amplified in multiple WGMs and shows peaks that are polarized and have linewidths Δλ as narrow as 0.33 nm and spectral power densities as high as 8 mW cm-2 nm-1. Considering its small footprint of ∼1 μm and remarkable emission characteristics, this silicon light source constitutes a significant step ahead toward fully integrated on-chip silicon photonics.
CRIS-Team Scopus Importer:2023-03-07